The ALMA-CRISTAL Survey: Weak Evidence for Star-formation-driven Outflows in z ∼ 5 Main-sequence Galaxies - Jack E. Birkin; Justin S. Spilker; Rodrigo Herrera-Camus; Rebecca L. Davies; Lilian L. Lee; Manuel Aravena; Roberto J. Assef; Loreto Barcos-Muñoz; Alberto Bolatto; Tanio Diaz-Santos; Andreas L. Faisst; Andrea Ferrara; et al. (The Astrophysical Journal)
There is a broad consensus from theory that stellar feedback in galaxies at high redshifts is essential to their evolution, alongside conflicting evidence in the observational literature about its prevalence and efficacy. To this end, we utilize deep, high-resolution [C II ] emission-line data taken as part of the [C II ] resolved interstellar medium (ISM) in star-forming galaxies with the Atacama Large Millimeter/submillimeter Array (CRISTAL) survey. Excluding sources with kinematic evidence for gravitational interactions, we perform a rigorous stacking analysis of the remaining 15 galaxies to search for broad emission features that are too weak to detect in the individual spectra, finding only weak evidence that a broad component is needed to explain the composite spectrum. Additionally, such evidence is mostly driven by CRISTAL-02, which is already known to exhibit strong outflows in multiple ISM phases. Interpreting modest residuals in the stack at v ∼ 300 km s ^−1 as an outflow, we derive a mass outflow rate of ${\dot{M}}_{{\rm{out}}}$ = 26 ± 11 M _⊙ yr ^−1 and a cold outflow mass-loading factor of η _m = 0.49 ± 0.20. This result holds for the subsample with the highest star formation rate surface density (Σ _SFR > 1.93 M _⊙ yr ^−1 kpc ^−2 ), but no such broad component is present in the composite of the lower-star-formation-rate density subsample. Our results imply that the process of star-formation-driven feedback may already be in place in typical galaxies at z = 5, but on average are not strong enough to completely quench ongoing star formation.